Groundwater monitoring and management: status and options in Pakistan - Bhatti, Muhammad Tousif; Anwar, Arif A.; Aslam, Muhammad (Elsevier, 2017)
Due to extensive groundwater development in the recent past, Pakistan now faces enormous challenges of groundwater management as it struggles to ensure food security for its rapidly growing population. These management challenges require a re-balancing of surface and groundwater monitoring objectives and approaches in the country. This article presents the current status of the groundwater monitoring and management in Pakistan. A compelling case is presented for optimization of material resources in improving groundwater level and quality data by proposing to use farmer organizations as a source of crowd sourced groundwater information. The authors showcase new methods to collect groundwater data and demonstrate use of automatic recording instruments for groundwater monitoring in a tertiary canal command area in the Pakistan’s Punjab. The results suggest that the potential for broader impact by engaging farmer organization and expanding monitoring networks is attractive. A common concern about long term deployment of automatic instruments is that the observation wells are not purged before extracting water quality samples. The authors address this concern through a field experiment by utilizing capabilities of automatic recording instruments.